Chemical mapping of excitons in halide double perovskites - Biega, R-I; Chen, Y; Filip, MR; Leppert, L (American Chemical Society, 2023)
Halide double perovskites comprise an emerging class of semiconductors with tremendous chemical and electronic diversity. While their band structure features can be understood from frontier-orbital models, chemical intuition for optical excitations remains incomplete. Here, we use ab initio many-body perturbation theory within the GW and the Bethe–Salpeter equation approach to calculate excited-state properties of a representative range of Cs2BB′Cl6 double perovskites. Our calculations reveal that double perovskites with different combinations of B and B′ cations display a broad variety of electronic band structures and dielectric properties and form excitons with binding energies ranging over several orders of magnitude. We correlate these properties with the orbital-induced anisotropy of charge-carrier effective masses and the long-range behavior of the dielectric function by comparing them with the canonical conditions of the Wannier–Mott model. Furthermore, we derive chemically intuitive rules for predicting the nature of excitons in halide double perovskites using computationally inexpensive density functional theory calculations.